Performance Analysis of non Medical Employees (non asn employees) based on Reward System, Discipline, Motivation Working and Contract Status at Dr. Harjono S. General Hospital in Ponorogo - Eva Teguh Zulnoviana; Koesnadi; Nurwijayanti (Journal for Quality in Public Health, 2022)
The decline in the performance of health workers is caused by several factors, including the reward system, discipline, work motivation and work contract status. The purpose of this study was to analyze the performance of non-medical personnel (non-ASN employees) at Dr. Harjono S. General Hospital In Ponorogo. This research is a non-experimental research with the type of observational analysis research with a cross sectional approach. The sample in this study was 157 people. Sampling in this study was carried out by cluster random sampling, namely the sampling technique in groups. Sampling of this type is carried out based on certain groups / areas. Data analysis using univariate and bivariate analysis (chi-square statistical test). The results showed that there was a relationship between the reward system (p = 0.000), discipline (p = 0.000), work motivation (p = 0.006), and work contract status (good = 91%) with the performance of non-medical personnel at Dr. Harjono S. General Hospital In Ponorogo. The conclusion from the research is that there is a positive influence between the reward system, discipline, work motivation and employment contract status with the performance of non-medical personnel at Dr. Harjono S. General Hospital In Ponorogo.